Bioinspired Ether Cyclizations within a π‐Basic Capsule Compared to Autocatalysis on π‐Acidic Surfaces and Pnictogen‐Bonding Catalysts. Issue 47 (8th July 2021) - Hao, Xiaoyu; Li, Tian‐Ren; Chen, Hao; Gini, Andrea; Zhang, Xiang; Rosset, Stéphane; Mazet, Clément; Tiefenbacher, Konrad; Matile, Stefan
Abstract: While the integration of supramolecular principles in catalysis attracts increasing attention, a direct comparative assessment of the resulting systems catalysts to work out distinct characteristics is often difficult. Herein is reported how the broad responsiveness of ether cyclizations to diverse inputs promises to fill this gap. Cyclizations in the confined, π‐basic and Brønsted acidic interior of supramolecular capsules, for instance, are found to excel with speed (exceeding general Brønsted acid and hydrogen‐bonding catalysts by far) and selective violations of the Baldwin rules (as extreme as the so far unique pnictogen‐bonding catalysts). The complementary cyclization on π‐acidic aromatic surfaces remains unique with regard to autocatalysis, which is shown to be chemo‐ and diastereoselective with regard to product‐like co‐catalysts but, so far, not enantioselective. Abstract : Breaking the rules : Thanks to their broad responsiveness, epoxide‐opening ether cyclizations are identified as ideal for the direct comparison of supramolecular catalysts. The results suggest that π‐basic supramolecular capsule catalysts are as outstanding as pnictogen‐bonding catalysts in breaking the Baldwin rules with high diastereoselectivity, particularly in cyclization cascades leading to bicyclic products. In clear contrast, chemo‐ and diastereoselective co‐ and autocatalysis is confirmed to be unique for anion‐π interactions.